Quality Evaluation of Chili Flakes by Variation of Packaging and Storage Temperature - David Yudianto; Prasetyo Wahyu Widhisono; Shofi Dwika Adha; Nurhasanah Nurhasanah; Sri Hadisetyana (jurnal makanan tropis dan teknologi agroindustri, 2020)
Chili processing is conducted to avoid damages due to its indigenous metabolic process of the product or external factors. Chili flakes are dried and crushed chili, continued by packaging in polyethylene terephthalate (PET) bottle and vacuum metalized polyethylene terephthalate (VMPET) sachet. One of the factors that influence product quality parameters during distribution in market are type of packaging and storage temperature. Usually retailers store chili flakes at various temperatures leading to an necessary of evaluation for the ability of packaging to be able to maintain the quality of chili flakes during the marketing process. This evaluation aims to determine the quality of chili flakes packaged by PET bottles and VMPET sachets at storage temperatures of 27°C and 35°C. Evaluation is conducted as long as 0, 7, 14, and 21 days. The chili flakes sample is evaluated in two stages. The first stage is preparation which involves samples preparation. The second stage is evaluation which includes physical, microbiological and organoleptic evaluation. Samples in 35°C storage temperature have lower water content compared to 27°C storage temperature. The PET packaging tends to leak compared to VMPET. Total microbes by PET packaging are higher than VMPET. Storage temperature of 35°C tends to have a higher total microbial yield than 27°C storage temperature. Investigation from organoleptic evaluation informs that on 21st storage day at 35°C has decrease on taste quality. Based on the all evaluations, it can be concluded that VMPET packaging tends to be more able to maintain the quality of chili flakes during the storage process. Type of VMPET packaging and storage temperatures of 27°C or lower can be used as recommendations for storing chili flakes products.